Does Flower Morphology affect Honey Bee Preference? - Lofing, Madison; Kim, Tania (My University, 2018)
Considering honey bee populations are at threat of declining. Flower preference is important to understand how we can attempt to preserve their habitats. The difference in abundance and time spent on composite vs non composite flowers is important to know in order to conserve habitats, and since bees are important for helping flowers and plants reproduce. Will composite flowers have more honey bees than non composite flowers? Composite flowers had significantly more honey bees than non composite flowers and the honey bees tended to stay longer as well. With more knowledge on flower preference we can take steps to restore habitats for honey bees, and improve agriculture. The purpose of this research is to gain a better understanding of flower preference in honey bees in order to maintain their habitats.
Keywords: Fall 2018